Embracing Diversity in the Classroom: Teachers’ Perceptions on Culturally Responsive Classroom Practices in Türkiye - Mercan Kucukakın, Pınar; Yildirim Tasti, Ozlem; Cobanoglu, Rahime; Gokmenoglu, Tuba; Akcaoglu, Mustafa Ozturk (Education and urban society, 2025)
Creating culturally responsive learning environments stands as a pivotal objective for 21st-century classrooms to foster inclusive and equitable education. This phenomenological inquiry explores the perceptions and practices of classroom teachers regarding Culturally Responsive Pedagogy (CRP) within the educational context of Türkiye. To this end, semi-structured interviews were conducted with 11 teachers purposefully selected from public schools in Gaziantep, a city notable for its increased cultural diversity in the country. Content analysis was utilized for data analysis. The following themes emerged in the study: Barriers to Culturally Responsive Pedagogy and Culturally Responsive Pedagogy Practices. The findings indicate that, although there are instances of culturally responsive practices being implemented and positive perceptions of CRP among educators, substantial challenges persist in integrating CRP effectively within classroom settings. The study highlights the need for effective professional development and teacher training focused on CRP.